Regioselective Mono‐aza‐Michael Additions of Divinyl Ketones with Benzotriazole and Other N‐Heterocycles. (17th August 2017) - Li, Zheng; Li, Jiasheng; Fu, Rugang; Xie, Demeng; Song, Geyang; Song, Wenli; Yang, Jingya
Abstract : The mono‐aza‐Michael additions of divinyl ketones with benzotriazole and other N ‐heterocycles in the presence of cesium carbonate were described. This protocol has advantages of high regioselectivity, high yield, and mild condition. Abstract :